2019
DOI: 10.1002/esp.4625
|View full text |Cite
|
Sign up to set email alerts
|

Topographic change and numerically modelled near surface wind flow in a bowl blowout

Abstract: A number of studies have measured and numerically modelled near surface wind velocity over a range of aeolian landforms and made suppositions about topographic change and landform evolution. However, the precise measurement and correlation of flow dynamics and resulting topographic change have not yet been fully realized. Here, using repeated high‐resolution terrestrial laser scanning and numerical flow modelling within a bowl blowout, we statistically analyse the relationship between wind speed, vertical wind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…From very oblique angles wind flow becomes separated as it enters the deflation basin over the landforms steep trailing arms, forming complex patterns of flow reversal and steering. Similar wind flow behaviour has been documented within the parabolic dune modelled by Finnigan et al (1990) and in bowl blowouts where incident wind flow enters over a steep erosional wall (Hesp and Walker, 2012;Smyth et al, 2012;Yurk et al, 2014;Smyth et al, 2019).…”
Section: Discussionsupporting
confidence: 72%
“…From very oblique angles wind flow becomes separated as it enters the deflation basin over the landforms steep trailing arms, forming complex patterns of flow reversal and steering. Similar wind flow behaviour has been documented within the parabolic dune modelled by Finnigan et al (1990) and in bowl blowouts where incident wind flow enters over a steep erosional wall (Hesp and Walker, 2012;Smyth et al, 2012;Yurk et al, 2014;Smyth et al, 2019).…”
Section: Discussionsupporting
confidence: 72%
“…Computational Fluid Dynamics (CFD) modelling of wind flow has become a common tool to predict and understand secondary wind flow and resulting sediment transport over aeolian landforms (Smyth, 2016). One of the important advantages of CFD is to permit visualisation of wind flow in these zones of complex flow, providing researchers rapid insight into a range of flow phenomena such as wind flow steering, acceleration and deceleration on the foredune (Hesp et al, 2015), and blowouts (Smyth, Jackson, & Cooper, 2012; Smyth et al, 2019; Smyth, Jackson, & Cooper, 2013). The current study uses CFD to provide three‐dimensional flow patterns, wind direction and wind speed, from the beach through the notch.…”
Section: Methodology and Methodsmentioning
confidence: 99%
“…During the last decade, flow–form–sand transport interactions have been studied on various coastal dune landforms, including foredunes (de Winter et al, 2020; Delgado‐Fernandez et al, 2013; Hesp & Smyth, 2016; Hilton et al, 2016; Jackson et al, 2013, 2011; Lynch, Jackson, & Cooper, 2009; Lynch, Jackson, & Cooper, 2010; Petersen, Hilton, & Wakes, 2011; Schwarz et al, 2021; Wakes, Bauer, & Mayo, 2021; Wakes, Hilton, & Konlechner, 2016; Wakes et al, 2010; Walker et al, 2017), foredune scarps (Hesp & Smyth, 2019; Piscioneri, Smyth, & Hesp, 2019), blowouts (Garès & Pease, 2015; Hesp & Walker, 2012; Hugenholtz & Wolfe, 2009; Pease & Gares, 2013; Smyth, Jackson, & Cooper, 2012; Smyth, Jackson, & Cooper, 2013; Smyth et al, 2019; Smyth, Jackson, & Cooper, 2014), parabolic dunes (Anderson & Walker, 2006; Delgado‐Fernandez et al, 2018; Hansen et al, 2009; Smyth et al, 2020; Wakes, 2013), nebkha (Hesp & Smyth, 2017; Zhao et al, 2019, 2020, 2021), sand cays (Hilton et al, 2019), beaches with large woody debris (Grilliot, Walker, & Bauer, 2018; Grilliot, Walker, & Bauer, 2019), and beach scarped ridges (Smyth & Hesp, 2015). These studies have contributed to our understanding of flow–form–sand transport relationships in a wide range of aeolian situations.…”
Section: Introductionmentioning
confidence: 99%
“…The renormalization process enables the Navier-Stokes equations to account for smaller scales of motion than the standard k-ε model, which employs a single turbulence length scale (Smyth, 2016). Previous work has shown that the k-ε RNG turbulence model modelled wind flow well, compared with field observations, over complex dune landforms such as a foredune (Hesp et al, 2015;Pattanapol et al, 2011;Wakes et al, 2010), blowouts (Smyth et al, 2012(Smyth et al, , 2019 and parabolic dunes (Delgado-Fernandez et al, 2018;Smyth et al, 2020;Wakes et al, 2016). A second-order spatial discretization scheme was employed to interpolate values between cell centres, and calculations were considered complete once the initial residual of each iteration was <0.0001 m s À1 for U X , U Y and U Z .…”
Section: Cfd Simulationsmentioning
confidence: 99%